Construction and Immunogenicity of Modified mRNA-Vaccine Variants Encoding Influenza Virus Antigens - Starostina, Ekaterina V. (Vaccines (Basel), 2021)
Nucleic acid-based influenza vaccines are a promising platform that have recently and rapidly developed. We previously demonstrated the immunogenicity of DNA vaccines encoding artificial immunogens AgH1, AgH3, and AgM2, which contained conserved fragments of the hemagglutinin stem of two subtypes of influenza A—H1N1 and H3N2—and conserved protein M2. Thus, the aim of this study was to design and characterize modified mRNA obtained using the above plasmid DNA vaccines as a template. To select the most promising protocol for creating highly immunogenic mRNA vaccines, we performed a comparative analysis of mRNA modifications aimed at increasing its translational activity and decreasing toxicity. We used mRNA encoding a green fluorescent protein (GFP) as a model. Eight mRNA-GFP variants with different modifications (M0–M7) were obtained using the classic cap(1), its chemical analog ARCA (anti-reverse cap analog), pseudouridine (Ψ), N6-methyladenosine (m6A), and 5-methylcytosine (m5C) in different ratios. Modifications M2, M6, and M7, which provided the most intensive fluorescence of transfected HEK293FT cells were used for template synthesis when mRNA encoded influenza immunogens AgH1, AgH3, and AgM2. Virus specific antibodies were registered in groups of animals immunized with a mix of mRNAs encoding AgH1, AgH3, and AgM2, which contained either ARCA (with inclusions of 100% Ψ and 20% m6A (M6)) or a classic cap(1) (with 100% substitution of U with Ψ (M7)). M6 modification was the least toxic when compared with other mRNA variants. M6 and M7 RNA modifications can therefore be considered as promising protocols for designing mRNA vaccines.